An Improved Public Key Encryption Algorithm Based on Chebyshev Polynomials - Jinhui Sun; Geng Zhao; Xufei Li (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper proposes an improved public key encryption algorithm based on Chebyshev polynomials. On the base of the semi-group property of Chebyshev polynomials, we import the alternative multiply coefficientto forge the ciphertext tactfully which can make the cipher text-only aattack out of work. The chosen of is decided by the the value of, and the number of can be chosen as required. Besides, The digital signature of the ciphertext not only can prevent the result from faking and tampering attack, but also  can make the algorithm have the function of identity authentication. Experimental results and performance analyses show that the improved algorithm has much higher security and practical value. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2035